Development Of Android-Based Interactive Jobsheet On Electrical Measuring Equipment Materials In Vocational School - Badruttamam, Muhammad; Hadromi, Hadromi (Universitas Negeri Semarang, 2021)
This study aims to 1) the feasibility of the developed android-based interactive jobsheet, 2) the effectiveness of the developed android-based interactive jobsheet. 3) Student responses to the developed android-based interactive worksheets. This study uses the ADDIE development model. The experimental design in this study used the One-Group Pretest-Postest Design. The research sample was class X students majoring in Light Vehicle Engineering (TKR). Data analysis used normality test, homogeneity test, product feasibility test and student response analysis. The results of the analysis can be obtained that the android-based interactive jobsheet development results are stated 1) feasible both from the results of the material test and media test with an average score of 80.6% and 81.25%. 2) Effectively used in learning as evidenced by the acquisition of an N-gain of 0.52 and is categorized as a moderate increase in learning outcomes. 3) Student responses to the android-based interactive worksheets that have been developed meet the